2006
DOI: 10.1002/jrs.1491
|View full text |Cite
|
Sign up to set email alerts
|

Linewidth modelling of C2H2N2 mixtures tested by rotational CARS measurements

Abstract: The acetylene-nitrogen system is investigated in a combined theoretical and experimental effort in view of its thermometry applications. Accurate values of the rotational Raman linewidths of acetylene are of crucial importance for the computation of spectra from rotational coherent anti-Stokes Raman scattering (CARS) used for temperature and concentration evaluations. Since the direct measurements of these linewidths are not available, they are rigorously calculated by a semi-classical Robert-Bonamy formalism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 23 publications
(26 reference statements)
1
22
0
Order By: Relevance
“…In addition the detection of other major species e.g. [131] has been reported. Since neither the pump nor the Stokes frequencies correspond to allowed single photon transitions the excitation is achieved via a two-photon process.…”
Section: Coherent Anti-stokes Raman Scatteringmentioning
confidence: 98%
“…In addition the detection of other major species e.g. [131] has been reported. Since neither the pump nor the Stokes frequencies correspond to allowed single photon transitions the excitation is achieved via a two-photon process.…”
Section: Coherent Anti-stokes Raman Scatteringmentioning
confidence: 98%
“…(3) up to L 1 ¼L 2 ¼4 (see for instance Refs. [11,[18][19][20]22] and references therein). We have checked that higher multipolar components of the PES do not provide any significant contributions to such calculations of the pressure broadening coefficients.…”
Section: Semi-classical Robert-bonamy Methodsmentioning
confidence: 99%
“…Due to the interest of the C 2 H 2 -N 2 system many theoretical calculations of the nitrogen broadening of acetylene lines have also been performed [1,3,4,[8][9][10][11]. However, these calculations were almost all conducted with the semi-classical method of Robert and Bonamy [12] using semi-empirical potentials.…”
mentioning
confidence: 99%
“…7 In view of the importance of the C 2 H 2 molecule, several recent experimental and theoretical works have been devoted to the determination of Raman linewidths. [8][9][10][11] Vereschagin et al reported the self-broadening coefficients of ν 2 Q-branch odd-J lines from 7 to 15, determined using vibrational CARS spectroscopy. 10 Domenech et al reported measurements of Ar-broadening coefficients associated with the same vibrational manifold at different temperatures using high-resolution stimulated Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%